Cross-linguistic Influence of image schema on Chinese EFL learners’ acquisition of the spatial preposition ‘in’ - Huang Xiaoqiong; Soo Ruey Shing (Universitas Syiah Kuala, 2026)
English spatial prepositions present challenges for EFL learners due to context dependence, lack of direct equivalence, conceptual differences, and other contributing factors. This study investigates how cross-linguistic similarities and differences in image schema relations between figure and ground (e.g., containment) influence Chinese EFL learners’ acquisition of preposition ‘in’, revealing the cognitive processes underlying conceptual transfer and its pedagogical implications. An explanatory sequential mixed-methods approach was employed, combining quantitative analysis from a picture-based test with qualitative insights from introspective interviews. A total of 150 Chinese university students, selected via a background questionnaire and a vocabulary test, were grouped into three English proficiency levels. The test examined learners’ use of ‘in’ across seven contexts, categorized according to cross-linguistic similarities and differences between ‘in’ and its Chinese equivalent ‘li’, based on container categorization and prototype theory. Cross-linguistic similarity and difference served as the independent variable, with proficiency functioning as a moderating factor. Semi-structured interviews explored the cognitive mechanisms underlying L1 conceptual transfer across four key themes. The results indicate that context and proficiency jointly influenced the use of ‘in’. Cross-linguistic similarities (e.g., Contexts I, IV, VI, VII) facilitated positive transfer, whereas differences (e.g., Contexts II, III, V) resulted in negative transfer. Although higher proficiency generally increased overall accuracy, Contexts II and III deviated from this pattern because learners were unaware of conceptual errors. The findings suggest that task-based learning, explicit instruction, and VR-enhanced input may help address conceptual transfer challenges, emphasizing the value of incorporating conceptual transfer theory into language teaching.